Assessment of Higher Education Institutions’ Social Responsibility Towards Transforming Lives of Deprived Local Communities: : A Community Engagement Approach - Madodi, Mussa (Papanda Publisher, 2025)
Despite the Tanzanian Government’s efforts in promoting its Higher Education Institutions (HEIs) to address problems facing their surrounding communities, the strategy has insufficiently institutionalized to bring the expected results. This study is an endeavor to have an assessment of Community Engagement Program which was established as among the strategies of stimulating the Community Development Training Institutes (CDTIs) and Community Development Technical Training (CDTTIs) to perform their Social Responsibilities. A cross- sectional research design was adopted to obtain a sample of 160 respondents. Data were collected using Questionnaires, Key Informants’ Interview (KII) and Focus Group Discussions (FGDs) methods and analyzed by using SPSS and content analysis. The study revealed that, financial budget allocated to facilitate the program operations is insufficient. Subsequently the insufficient budget is negatively influencing the program implementers to find shortcuts in following the program operational procedures as a result some of the felt needs of the intended beneficiaries are precluded. Moreover, the program’s undertakings are inadequately disclosed to attract support from other potential development partners. In order for the program to effectively accomplish the ideal objective of its establishment, it is recommended the government in collaboration with other stakeholders to mobilize and inject sufficient financial and other related resources.